POSSIBLE REASONS FOR THE REDUCTION IN POPULATION OF THE GREATE GERBIL RHOMBOMYS OPIMUS LICHTENSTEIN, 1823 IN THE PREUSTURT AUTONOMOUS PLAGUE FOCUS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In the course of research on the territory of the PreUstyurt autonomous plague focus in 2017-2021 a decrease of the number of great gerbils was revealed. The main reason is theinfluence of unfavorable external factors, including weather conditions (drought), which led to adecrease in the density of rodent settlements and, as a result, to a change in the structure of populations.
Keywords: rodents, fleas, great gerbil, abundance, reproduction, mortality, plague, epizootics, weather conditions.